2016
DOI: 10.1108/md-09-2014-0574
|View full text |Cite
|
Sign up to set email alerts
|

Board diversity and R & D investment

Abstract: Purpose -The purpose of this paper is to investigate the effect of board diversity on the extent to which firms invest in R&D.Design/methodology/approach -empirical analysis of 175 firm-year observations for Fortune 500 firms in high tech industries and the four different indications of diversity of their boards.Findings -Boards that can tap into a diversity of sources for information can be expected to make better decisions. Diversity in a team and a board can, however, also impede team performance.Measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
115
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 52 publications
5
115
1
Order By: Relevance
“…Similarly, Almazan et al [29] and others reported that CEO compensation influenced the level of R&D expenditure of firms [30][31][32]. In a recent study, Midavaine et al [32] reported that board diversity, such as their tenure, education, and gender, also relate to firms' decisions on R&D investment.…”
Section: Impact Of Related Party Transactions On Randd Investmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Almazan et al [29] and others reported that CEO compensation influenced the level of R&D expenditure of firms [30][31][32]. In a recent study, Midavaine et al [32] reported that board diversity, such as their tenure, education, and gender, also relate to firms' decisions on R&D investment.…”
Section: Impact Of Related Party Transactions On Randd Investmentmentioning
confidence: 98%
“…Jensen and Meckling [27] has stated that managers tended to avoid high-risk investment, as its ownership was lower, in order to avoid private costs and enhance their personal utilities, while managerial ownership or managerial incentive can act as a determinant when defining R&D expenditure [28]. Similarly, Almazan et al [29] and others reported that CEO compensation influenced the level of R&D expenditure of firms [30][31][32]. In a recent study, Midavaine et al [32] reported that board diversity, such as their tenure, education, and gender, also relate to firms' decisions on R&D investment.…”
Section: Impact Of Related Party Transactions On Randd Investmentmentioning
confidence: 99%
“…In the same vein, Midavaine et al (2016) examine the influence of two types of management team diversity on R&D investment: information-based diversity (education and tenure) and personalbased diversity (age, gender). Information-based diversity refers to cognitive abilities; that is, to attributes reflecting managers' ability to select and process relevant information (Midavaine et al, 2016).…”
Section: Executive Management Diversitymentioning
confidence: 99%
“…Information-based diversity refers to cognitive abilities; that is, to attributes reflecting managers' ability to select and process relevant information (Midavaine et al, 2016).…”
Section: Executive Management Diversitymentioning
confidence: 99%
See 1 more Smart Citation